Can God be trusted? : faith and the challenge of evil - Stackhouse, John G. (John Gordon), 1960- (Oxford, NY Oxford University Press, 1998)
"In a world riddled with disappointment, malice, and tragedy, what rationale do we have for believing in a benevolent God? If God is all-powerful and all-loving, why is there so much evil in the world? John Stackhouse goes beyond Rabbi Kushner, M. Scott Peck, and others to take a more historically informed approach to this dilemma, examining what philosophers and theologians have said on the subject and offering reassuring answers for thoughtful readers." "John Stackhouse explores how great thinkers have grappled with the problem of evil - from the Buddha, Confucius, Augustine, and David Hume to Martin Luther, C.S. Lewis, Alvin Plantinga, and others - and grounds his analysis in everyday examples. Stackhouse examines, clearly and concisely, what the best minds have had to say on these questions and, boldly affirms that the benefits of evil, in fact, outweigh the costs. Finally, he points to Christian revelation - which promises the transformation of suffering into joy - as the best guide to God's dealings with the world."--Jacket.
pt. 1: Problems -- Is there a problem? -- What is evil? -- Further problems -- pt. 2: Responses -- Other angles -- A good world after all? -- The fork in the road -- Thinking and living.
Includes bibliographical references (pages 177-191) and index.
Keywords: Theodicy; Good and evil; Trust in God -- Christianity